ANALYSIS OF THE HEALTH LEVEL OF ISLAMIC BANKING FINANCIAL PERFORMANCE THROUGH THE RGEC APPROACH IN 2017-2022 - Nur Maulidah Dini Rahmani; Muhammad Iqbal Surya Pratikto (Nurul Jadid University, 2024)
Through the distribution of funds, banking helps increase investment and economic growth. This gives banking a crucial role in supporting Indonesia's economy. The funding provided by banks to small and medium-sized enterprises, which are important economic resources for Indonesia, underscores this role. Therefore, bank management must strive to maintain a proper balance between ensuring sufficient liquidity, achieving reasonable profitability, and ensuring adequate capital. To assess the health of a bank, several methods can be used according to its development, one of which is based on Bank Indonesia Regulation No. 13/1/PBI/2011 concerning the Assessment of Commercial Bank Soundness Levels. Bank Indonesia has established a risk-based bank soundness rating system. According to Financial Services Authority Regulation (POJK) No. 8/POJK.3/2014, the factors used in the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) form the basis of the assessment. This study uses a quantitative method with a descriptive approach. The data used were obtained from secondary sources, primarily the financial reports of the Islamic Business Unit (UUS) for three consecutive years from 2017 to 2022, accessed through the OJK website. The results of the study show that CIMB Niaga Syariah Bank's condition during the 2017-2022 period is as follows: for the risk profile factor with the NPF ratio, it received a very healthy rating; with the FDR ratio, it received an unhealthy rating; for the GCG factor with the PDN ratio, it received a fairly healthy rating; for the earnings factor with the ROA ratio, it received a very healthy rating; with the ROE ratio, it received a fairly healthy rating; with the NI ratio, it received a healthy rating, and with the BOPO ratio, it received a very healthy rating; and for the capital factor with the CAR ratio, it received a very healthy rating.